Analisis Kemampuan Menulis Teks Biografi Siswa Pada Model Pembelajaran Project Based Learning - Mei Indra Dewi; Cahyo Hasanudin; Sutrimah Sutrimah (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesian language learning includes four aspects of language skills, namely listening skills, speaking skills, reading skills and writing skills, writing is a language skill that aims to convey information in writing through graphic symbols that are clear and easy to understand by readers. The purpose of this study is to explain and describe the structure of the biographical text, namely the orientation of important events and reorientation. This description uses a case study approach, which is a method that aims to analyze and understand a phenomenon or problem in depth and comprehensively. This study uses data analysis techniques based on the Miles and Huberman model, namely through the process of data reduction, data presentation, and drawing conclusions.